Analysis Of Students' Mathematical Problem-Solving Ability Based On Polya's Stages Viewed From Mathematical Resilience - Isna Fauziyah; Elah Nurlaelah; Jarnawi Afgani Dahlan; Toyib Febri Kisdiono (Universitas Wiralodra, 2025)
Mathematics learning should facilitate students in developing and exploring their Mathematical Problem-Solving Ability (MPSA). Mathematical resilience is very important in supporting students’ MPSA in mathematics learning. This study aims to explore students’ MPSA in terms of their mathematical resilience. A qualitative descriptive method was used in this research to analyze the contribution of mathematical resilience to students’ MPSA. A senior high school in Lebak Regency, Banten, was chosen as the location for the research. The research sample consisted of 23 eleventh-grade students, from which 3 students were selected for further analysis based on high, medium, and low categories of mathematical resilience. The findings indicate that students with high mathematical resilience have very good MPSA, as evidenced by achieving all four indicators of MPSA based on Polya’s problem-solving stages. Students with medium mathematical resilience still require guidance at the fourth stage of Polya's process, namely evaluating the results and the problem-solving process. Meanwhile, students with low mathematical resilience are only able to understand the problem but are not yet able to develop strategies, implement problem-solving, or evaluate the results and the process. Based on the findings, it can be concluded that students’ mathematical resilience influences their MPSA, thus requiring attention to mathematical resilience in the mathematics learning process.